1985
DOI: 10.1111/j.1600-0722.1985.tb01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary S treptococcus mutans count and gingivitis in children after rinsing with a chlorhexidine‐fluoride solution with and without strontium

Abstract: Thirty schoolchildren, 9–12 yr old with high DMF score, rinsed their mouths twice a day for 3 days with a chlorhexidine‐fluoride (CXF) solution or a chlorhexidine‐fiuoride‐strontium (CXFSr) solution. Streptococcus mutans counts (CFU) were made from saliva incubated on MSB agar and the gingival bleeding was recorded both before and after the rinsing period. S. mutans count decreased significantly immediately after the rinsing with each of the solutions (from 650 × 103 to 170 × 103 CFU/ml by CXF and from 500 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
5
11
0
Order By: Relevance
“…The present results confirm the suggestions of many authors [Luoma, 1975;Emilson et al, 1976;Brayer et al, 1977;Dolles and Gjermo, 1980;Katz, 1982;Spets-Happonen et al, 1985] that CHX and F, in a combination, exert a synergistic effect with re gard to cariogenic bacteria. This effect appears to be mainly a toxic one and is merely due to the mode of action of CHX.…”
Section: Discussionsupporting
confidence: 81%
“…The present results confirm the suggestions of many authors [Luoma, 1975;Emilson et al, 1976;Brayer et al, 1977;Dolles and Gjermo, 1980;Katz, 1982;Spets-Happonen et al, 1985] that CHX and F, in a combination, exert a synergistic effect with re gard to cariogenic bacteria. This effect appears to be mainly a toxic one and is merely due to the mode of action of CHX.…”
Section: Discussionsupporting
confidence: 81%
“…The best effects have been obtained when an extra layer of polyurethane sealant (Sandham et al, 1988 or bonding resin (Fure and Emilson, 1990) has been applied over the chlorhexidine varnish, which increased the retention of chlorhexidine on the teeth for up to approximately five days . Without an extra layer, the long-term effect seems to be highly dependent on the concentration of Based ondata from: Emilson, 1981;Emilson and Fornell, 1976;Emilson etal.,1976;FureandEmilson,199a,Gisselssonetal.,1988Johansen et al, 1975Katz, 1982;Keltjens et al, 1990;Kristoffersson and Bratthall, 1982;Lindquist et al, 1989, Luoma et al, 1978Maltz et al, 1981;Mikkelsen et al, 1981;Ostela et al, 199Q0 Persson et al, 1991;Petersson et al, 1991;Sandham et al, 1988Sandham et al, ,1991Schaeken and De Haan, 1989, Schaeken et al, 1986, 1991aSpets-Happonen et al, 1985von der Fehr et al, 1975;Zickert et al, 1982;Zyskind et al, 1990. chlorhexidine in the varnish. A dose-response effect has been observed in plaque studies in which a varnish containing 40% chlorhexidine was found to be more effective against mutans streptococci than a varnish containing either 10 or 20% or 25 or 33% (Schaeken et al, 1991b).…”
Section: Effects Of Different Modes Of Treatmentmentioning
confidence: 97%
“…Table 4 summarizes the effects of different modes of chlorhexidine treatment which have been used to reduce mutans streptococci and dental caries in humans. Chlorhexidine used as a mouthrinse (Mikkelsen et al, 1981;Spets-Happonen et al, 1985;Persson et at., 1991) or in dental gels applied by toothbrushing (Emilson and (3) 1994 result in a low to moderate reduction in mutans streptococci counts in plaque and saliva and in only a trend toward less caries. The small effect on mutans streptococci and surfaces at risk probably reflects re-growth of mutans streptococci because the reservoirs in the dentition are not sufficiently affected due to the low bio-availability of chlorhexidine from the mouthrinse solution and dentifrice.…”
Section: Effects Of Different Modes Of Treatmentmentioning
confidence: 99%
“…However, the subjects had low or moderate caries activity. [8][9] After these early studies, conducted more than 20-25 years ago, there are very few published articles that describe evaluations of the effect of chlorhexidine rinse on caries. One clinical study by Spets-Happonen and others, 10 where the use of periodic chlorhexidine mouthwashes was followed over a period of two years and nine months, revealed no significant reduction in caries.…”
Section: Mouthrinsesmentioning
confidence: 99%